2016
DOI: 10.4067/s0716-10182016000400015
|View full text |Cite
|
Sign up to set email alerts
|

Evidencia serológica retrospectiva de infecciones por Leptospira spp., dengue, hantavirus y arenavirus en indígenas Emberá-Katío, Colombia

Abstract: Evidencia serológica retrospectiva de infecciones por Leptospira spp., dengue, hantavirus y arenavirus en indígenas Emberá-Katío, Colombia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…In our country, there is certainty that the Guanarito virus circulates in rodents in the department of Córdoba, but so far there have been no cases of diagnosed human infection (10). A 3.1% seroprevalence of IgC arenavirus antibodies was reported in the Emberá-Katio community in the alto Sinú region (Colombia) (11). Another study conducted in Sincelejo (Colombia) found a 10% seroprevalence, and the lymphocytic choriomeningitis genome was detected in 16 brain samples of Mus musculus rodents (12).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In our country, there is certainty that the Guanarito virus circulates in rodents in the department of Córdoba, but so far there have been no cases of diagnosed human infection (10). A 3.1% seroprevalence of IgC arenavirus antibodies was reported in the Emberá-Katio community in the alto Sinú region (Colombia) (11). Another study conducted in Sincelejo (Colombia) found a 10% seroprevalence, and the lymphocytic choriomeningitis genome was detected in 16 brain samples of Mus musculus rodents (12).…”
Section: Introductionmentioning
confidence: 82%
“…En nuestro país, existe certeza de que el virus Guanarito circula en roedores en el departamento de Córdoba, pero hasta el momento no existen casos diagnosticados en humanos (10). En una comunidad indígena Emberá-Katio, del alto Sinú (Colombia), se reportó una seropositividad del 3.1% para anticuerpos IgG de arenavirus (11). Otro estudio realizado en Sincelejo (Colombia) encontró una seroprevalencia del 10% y se detectó el genoma del virus de la coriomeningitis linfocítica en 16 muestras de cerebro, de roedores Mus musculus (12).…”
Section: Introductionunclassified
“…Thus, conducting prospective studies to analyze and detect potential areas at risk of transmission of tropical diseases, as well as estimating risk and protective factors for subsequent interventions, are becoming increasingly necessary. The Urabá region in the Department of Antioquia, Colombia, is considered a potential endemic region for tropical diseases such as malaria, leishmaniasis, dengue viruses, leptospirosis, and rickettsiosis, among others 15,23,24 . Therefore, analyzing seropositivity outcomes for more than one disease when conducting analytical observational studies could broaden the understanding of factors for those tropical and neglected diseases potentially endemic in this region.…”
Section: Discussionmentioning
confidence: 99%
“…In Colombia, Pichindé virus, an arenavirus whose reservoirs are Nephelomys albig-ularis (previously called Oryzomys albigularis ) rodents, is actively circulating, and apparently, it is not associated with human infection [ 19 , 20 ]. However, serological studies performed in three regions of Antioquia, Cesar, and Córdoba departments have evidenced seropositivity to mammarenaviruses among different population groups ( Table 1 ) [ 21 , 22 , 23 ], as well as one possible case of arenaviral infection in which seroconversion was evidenced ( Figure 1 A) [ 21 ]. These findings suggest that another arenaviruses may be present in Colombia, which apparently can be infective for humans.…”
Section: Arenavirusmentioning
confidence: 99%
“…Furthermore, several serological studies performed in different Colombian regions have evidenced human exposure to hantaviruses among different population groups, such as healthy inhabitants from six urban municipalities of Córdoba department [ 24 ], febrile patients in urban settlements of the Urabá region (Antioquia department) in whom no seroconversion was evidenced [ 21 ], and indigenous populations from rural communities of Córdoba (Embera Katío and Tuchín communities) and Cesar departments (Kankuamos community) [ 22 , 23 , 25 ], suggesting that at least one hantavirus native to Colombia is circulating among rural inhabitants and that, probably, another hantavirus might be present in urban regions ( Table 1 ) ( Figure 1 B). Exposure to hantaviruses has also been evidenced in several rodent species in the departments of Córdoba, Sucre, and Antioquia [ 50 , 51 , 52 ], as well as the description of a novel hantavirus designated as “Necoclí” virus [ 53 ], whose importance for human and animal health is still unknown.…”
Section: Hantavirusmentioning
confidence: 99%